Attributes affecting instructors’ performance: springboard for organizational development interventions - Paraggua, Victoria Q.; Paje, Brillo S. (Intelektual Pustaka Media Utama, 2025)
This study aimed to identify the attributes that motivate the training instructors to perform effectively as a basis in proposing organizational development interventions for Philippine Coast Guard-Coast Guard Education Training and Doctrine Command (PCG-CGETDC), Philippine Navy-Naval Education, Training and Doctrine Command (PN-NETDC), and Philippine Merchant Marine Academy-Training Center (PMMA-TC). The survey results identified thirty-one attributes that highly motivate the instructors to perform effectively where no significant difference among the responses was established. Among the top motivational attributes are alignment of professional goals with the organizational goals; communication between head and subordinates; observance of fair work practices; assistance in technical support; clear selection, recruitment, and promotion polices; and existence of evaluation and feedback system and quality management system. Conversely, a significant relationship between the respondents’ extent of agreement on the attributes affecting their performance and their profiles was revealed. The training instructors considered twenty-three organizational interventions very important. There is a significant difference between and within their responses as an institution. The strengths-weaknesses-opportunities-threats (SWOT) analysis and other related data, gathered through survey, were utilized to develop the proposed validated organizational development interventions for these maritime-related institutions.